A Implementation of COVID-19 Preventive Healthy Lifestyle (PHL) among Administration Staff and its association with Health Consciousness and Occupational Factors: A Cross Sectional Study in Faculty Medicine Universitas Indonesia - Tukimun, Suci Tria Meirisa; Kekalih, Aria; Purwito Adi, Nuri; Sumaryani Soemarko, Dewi; Ilyas, Muhammad (The Indonesian Journal of Community and Occupational Medicine, 2023)
Background: The COVID-19 pandemic has altered the pattern of human life toward a new life order,particularly in the office setting. Appeals, prohibitions, even large-scale social restrictions were implemented in order to decrease the cases. To cope with the rapid spread of the outbreak, citizens have to increase health consciousness and reduce their social interactions. The health consciousness require health protocols implementation. Ensuring high levels of compliance and several modifiable occupational risk factors in the office setting has been a challenge to manage the pandemic effectively. Methods: The research method used in this study is empirical research, by taking a problem-based approach to a behavioral approach namely health consciousness supported by primary data sourced from data sources. The data were obtained in October to November 2021. Results: When taken as a whole, the implementation of health protocols as part of the effort to prevent the spread of COVID-19 was relatively good; it's just that certain obstacles must be evaluated. The highest health consciousness scores were personal responsibility and health motivation. While the lowest of it were the psychological/inner state aspect and the health information and seeking usage. There was a positive correlation between the dimensions of health consciousness and several items of COVID-19 PHL (r > 0.3). The ease of applying COVID-19 PHL was significantly better for shift workers compared to non-shift workers, namely to severalitems of PHL. Based on the work pattern groups (WFH < 20 hours, WFH 20-40 hours and WFH > 40 hours, alternate to Work From Office (WFO)), there were no significance difference in the ease of implementation COVID-19 Preventive Healthy Lifestyle. Conclusion: Our results suggest that to effectively manage the pandemic, we should ensure that health consciousness is well-maintained, especially aspects of health information and seeking usage and psychological/inner state. Keywords: health consciousness, COVID-19 Preventive Healthy Lifestyle (PHL) at the workplace, shift work, work patterns during pandemic